THAT BALANCE-SHEET APPROACH. - Nelson, Edward G. (The Accounting Review, 1935)
All two frequently a university student begins the study of accountancy with a sample balance sheet. After he has mastered a few questionable definitions, he is introduced to the dynamics of business operations through the statement of profit and loss. Once the form and content of the two schedules are outlined, he may explore the records of bookkeepers at great length. In the end, he may have a comprehensive knowledge of ordinary procedures, but he is not, in any fundamental sense, prepared to appraise the work of an accountant. The accounting for a balance sheet may be explained, but the statement cannot be understood without first conceiving some elementary notion. Accountants do not act as though they believed assets to be property or the subject of property. The former, in its strict legal sense, is "the indefinite right of the user and the disposition which one may lawfully exercise over particular objects or things." The property holder has "rights to the chance of the future services of wealth. Wealth coupled with possession, is "the visible manifestations of invisible rights, the evidence of things not seen.